2008
DOI: 10.1086/587153
|View full text |Cite
|
Sign up to set email alerts
|

The Social Dynamics of Mathematics Coursetaking in High School

Abstract: This study examines how high school boys' and girls' academic effort, in the form of math coursetaking, is influenced by members of their social contexts. The authors argue that adolescents' social contexts are defined, in part, by clusters of students (termed "local positions") who take courses that differentiate them from others. Using course transcript data from the recent Adolescent Health and Academic Achievement Study, the authors employ a new network algorithm to identify local positions in 78 high scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
202
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(213 citation statements)
references
References 103 publications
10
202
0
1
Order By: Relevance
“…In sociology and public health, this approach typically involves identifying all the peers of each individual or specific peers, such those from whom one seeks advice or academic help (Scott & Carrington, 2011). Rather than using a class average, the peer influence variable is the average score of only the peers who were identified for each student (Frank et al, 2008).…”
Section: Measuring Peer Influencementioning
confidence: 99%
“…In sociology and public health, this approach typically involves identifying all the peers of each individual or specific peers, such those from whom one seeks advice or academic help (Scott & Carrington, 2011). Rather than using a class average, the peer influence variable is the average score of only the peers who were identified for each student (Frank et al, 2008).…”
Section: Measuring Peer Influencementioning
confidence: 99%
“…Current studies indicate that students who are assigned to high tracks accelerate their development, but their self-concept decreases, while those assigned to low track slow their progress, but their self-concept increases. Unfortunately, the low tracks schooled students are labeled by their peers and teachers as dumb (Frank et al 2008). In addition, as students have more relationships with the peers with whom they spend more time, this situation can lead low tracks students to engage in risk or criminal activity (Dishion et al 2001).…”
Section: Social and Cultural Ecology Of The Schoolmentioning
confidence: 99%
“…Levy-Tossman, Kaplan, & Assor [7] find the connection between academic motivation and social relationships. Frank et al [8] agree on the importance of peer influences and find that girls are highly responsive to the social norms in their local positions. Hasan and Bagde [9] found that peer effects are a consequential determinant of academic achievement.…”
Section: Introductionmentioning
confidence: 99%